Anatase titanium dioxide loaded polylactide membranous films: preparation, characterization, and antibacterial activity assessment - Dural-Erem, Aysin; Erem, Hasan Hakan; Ozcan, Gulay; Skrifvars, Mikael (Informa UK Limited, 2014)
In this study, the preparation method and characteristics of anatase titanium dioxide (TiO2) nanoparticle-loaded polylactide (PLA) films and their antibacterial efficacy against Klebsiella pneumoniae (ATCC 4352) and Staphylococcus aureus (ATCC 6538) bacterium were studied. A series of PLA nanocomposites containing, respectively, 0, 1, and 5% (wt.) titanium dioxide (TiO2) nanoparticles were prepared by melt intercalation method. The effect of TiO2 nanoparticles on the thermal and mechanical characteristics of the films was determined. Thermal analysis showed that the glass transition temperature, crystallization temperature, melting temperature, and decomposition temperatures (Td0.5 and Td0.05) decreased with the filler content. The results obtained from tensile tests showed that TiO2 nanoparticles reduced the mechanical properties and moduli of the PLA films. On the other hand, the water absorption properties of the nanocomposite films increased with the addition of nanoparticles and nanocomposite films e...